2015
DOI: 10.1017/s0960258515000070
|View full text |Cite
|
Sign up to set email alerts
|

A new seed coat water-impermeability mechanism in Chaetostoma armatum (Melastomataceae): evolutionary and biogeographical implications of physiophysical dormancy

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0960258515000070How to cite this article: Rafaella C. Ribeiro, Denise M.T. Oliveira and Fernando A.O. Silveira A new seed coat water-impermeability mechanism in Chaetostoma armatum (Melastomataceae): evolutionary and biogeographical implications of physiophysical dormancy. AbstractDetermining the phylogenetic and biogeographic distribution of physical dormancy remains a major challenge in germination ecology. Here, our goal was to describe a novel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
(52 reference statements)
0
3
1
1
Order By: Relevance
“…However weight increases by imbibition noticeably larger than the relatively small increases we found with C. ladanifer were reported in other species without effective passage of water through seed coat [67]. However the use of methyl violet showed that with few exceptions water uptake in C. ladanifer is not prevented by seed coats because the dye was found inside 93% seeds.…”
Section: Discussioncontrasting
confidence: 62%
“…However weight increases by imbibition noticeably larger than the relatively small increases we found with C. ladanifer were reported in other species without effective passage of water through seed coat [67]. However the use of methyl violet showed that with few exceptions water uptake in C. ladanifer is not prevented by seed coats because the dye was found inside 93% seeds.…”
Section: Discussioncontrasting
confidence: 62%
“…microrefugia and climate change (Cooper et al 2011;Keppel et al 2012;Ashcroft and Gollan 2013;Brendonck et al 2014;Mee and Moore 2014;Barrett and Yates 2015), the evolution of trees (Raven and Andrews 2010;Cramer 2012), clonality (Binks et al 2015), the occurrence of OCBISs (old, climatically buffered, infertile seascapes - Langlois et al (2012), significant gaps in Darwinian evolutionary theory (Hopper and Lambers 2009), old salt lake systems (Bui et al 2014a, b), and evolution of novel aquatic traits (Tuckett et al 2010;Davies and Stewart 2014). Seed biological studies are beginning to explore the relevance of Ocbil theory to their discipline (Tuckett et al 2010;Hidayati et al 2012;Wilman et al 2014;Alvarado et al 2015b;Edwards et al 2015;Ribeiro et al 2015).…”
Section: Citation Review Areas Of Focus In the Literature And Summarmentioning
confidence: 99%
“…Seeds of both species are probably dormant, but the type of dormancy is unknown. The dormancy types and metabolism in Melastomataceae are poorly known, although some studies have showed multiple dormancy [36], physiological dormancy [45] and water impermeability in seed coat [46]. The spreading of the germination through time, typical of seeds of several Melastomataceae, permits the inclusion of these seeds in the category of relative dormancy as proposed by Labouriau [47], but the type of dormancy is unclear because the spreading of the germination through time can be due to physical, morphological, physiological or combination of these causes.…”
Section: Discussionmentioning
confidence: 99%